Universal health care in Bangladesh—promises and perils - Adams, Allayne M; Ahmed, Syed Masud; Evans, Timothy G (The Lancet, 2022)
This article was published in The Lancet Global Health [© 2017 Creative Commons Attribution-NonCommercial – NoDerivs (CC BY-NC-ND 4.0) ] and the definite version is available at : https://doi.org/10.1016/S2214-109X(17)30470-9. The Journal's website is at: https://www.thelancet.com/journals/langlo/article/PIIS2214-109X(17)30470-9/fulltext